2015
DOI: 10.1186/s13019-015-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical management of a rare esophageal inflammatory myofibroblastic tumour: a case report

Abstract: Inflammatory myofibroblastic tumour (IMT) is an uncommon mesenchymal tumour, which can occur anywhere in the body, rarely in esophagus. Mostly, the diagnosis is postoperative, after the hispathological evaluation of the specimen. There are no definite guidelines regarding the diagnosis and management. Here, we report a 60 year old lady presenting with dysphagia, diagnosed to have a submucosal esophageal tumor with Barium esophagogram and contrast enhanced computed tomography. She was managed successfully with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…However, it is often difficult to obtain enough tissue using a transendoscopic biopsy to establish a definitive histological diagnosis (17). In the present patient, a gastroscopic biopsy of the lesion was inconclusive, and surgical resection of the tissues aided to obtain the final diagnosis of IMT.…”
Section: B a Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, it is often difficult to obtain enough tissue using a transendoscopic biopsy to establish a definitive histological diagnosis (17). In the present patient, a gastroscopic biopsy of the lesion was inconclusive, and surgical resection of the tissues aided to obtain the final diagnosis of IMT.…”
Section: B a Discussionmentioning
confidence: 74%
“…It has been previously reported that three histological patterns may coexist variably within the same tumor, namely myxoid/vascular, compact spindle cell and fibrous hypocellular (15,(18)(19)(20). Immunohistochemically, the majority of cases of IMT express SMA, desmin and cytokeratin (15,17,21). Anaplastic lymphoma kinase (ALK) immunostaining is detected in 40-60% of cases, and involves rearrangements or translocations of the ALK receptor tyrosine kinase on the chromosome 2p23 (16,21).…”
Section: B a Discussionmentioning
confidence: 99%
“…It is known to occur primarily in the viscera and soft tissue of children and young adults . They are now considered as intermediate‐grade tumor with a potential for recurrence . The etiology of IMT is controversial and thought to be an aberrant response to tissue injury .…”
Section: Discussionmentioning
confidence: 99%
“…They are now considered as intermediate‐grade tumor with a potential for recurrence . The etiology of IMT is controversial and thought to be an aberrant response to tissue injury . The commonly identified causes of IMTs include Epstein–Barr virus, human herpes virus eight, reflux, trauma, and overexpression of interleukin 6 .…”
Section: Discussionmentioning
confidence: 99%
“…6 On CT, the lesions show low attenuation on unenhanced image and shows progressive opacification after intravenous contrast. 7 Calcification may be present. MRI shows a low signal on T2 weighted images and delayed enhancement on T1 weighted image.…”
Section: Discussionmentioning
confidence: 99%